Thermal Analysis of a Perforated Vertical Wellbore - Mohammed, Haider Sami; Sultan, Hussein Sadiq; Khazal, Emad Abdullah (Basrah Journal for Engineering Sciences, 2022)
A numerical simulation of the effect evaluation of heat loss and temperature distribution along the wellbore is performed, for two models, the first is an open hole (without perforation) and the other is a perforated vertical wellbore. In this study, the Computational Fluid Dynamics (CFD) software code ANSYS FLUENT 15.0 has been used, for simulate a model of 3-D turbulent flow with stander k-ϵ model. The results of this show that, increasing the heat losses leads to an increase in the temperature gradient, while the temperature gradient decreases with increasing inlet main velocity. Also, the temperature of the produced crude oil decreases with increasing the length of the wellbore.